Fabrication of deep micro-holes in reaction-bonded SiC by ultrasonic cavitation assisted micro-EDM - Liew , Pay Jun; Yan , Jiwang; Kuriyagawa, Tsunemoto (Elsevier, 2014)
Ultrasonic vibration was applied to dielectric fluid by a probe-type vibrator to assist micro electrical discharge machining of deep micro-holes in ceramic materials. Changes of machined hole depth, hole geometry, surface topography, machining stability and tool material deposition under various machining conditions were investigated. Results show that ultrasonic vibration not only induces stirring effect, but also causes cloud cavitation effect which is helpful for removing debris and preventing tool material deposition on machined surface. The machining characteristics are strongly affected by the vibration amplitude, and the best machining performance is obtained when carbon nanofibers are added into the vibrated dielectric fluid. As test pieces, micro-holes having 10 μm level diameters and high aspect ratios (420) were successfully fabricated on reaction-bonded silicon carbide in a few minutes. The hybrid EDM process combining ultrasonic cavitation and carbon nanofiber addition is demonstrated to be useful for fabricating microstructures on hard brittle ceramic materials.